Impact of percutaneous mitral valve repair using the MitraClipTM system on ventricular arrhythmias and ICD therapies - Geis, Nicolas; Göbbel, Anna; Kreußer, Michael; Täger, Tobias; Katus, Hugo; Frey, Norbert; Schlegel, Philipp; Raake, Philip (Life, 2022)
Transcatheter edge-to-edge repair (TEER) using the MitraClip™ device has been established as a suitable alternative to mitral valve surgery in patients with severe mitral regurgitation (MR) and high or prohibitive surgical risk. Only limited information regarding the impact of TEER on ventricular arrhythmias (VA) has been reported. The aim of the present study was to assess the impact of TEER using the MitraClipTM device on the burden of VA and ICD (Implantable Cardioverter Defibrillator) therapies. Among 600 MitraClipTM implantations performed in our clinic between September 2009 and October 2018, we identified 86 patients with successful TEER and an active implantable cardiac device (pacemaker, ICD, CRT-P/D (Cardiac Resynchronization Therapy-Pacemaker/Defibrillator)) eligible for retrospective VA analyses. These patients presented with mainly functional MR (81.4%) and severely reduced left ventricular ejection fraction (mean LVEF 22.1% ± 10.3%). The observation period comprised 456 ± 313 days before and 424 ± 287 days after TEER. The burden of ventricular arrhythmias (sustained ventricular tachycardia (sVT) and ventricular fibrillation (VF)) was significantly reduced after TEER (0.85 ± 3.47 vs. 0.43 ± 2.03 events per patient per month, p = 0.01). Furthermore, the rate of ICD therapies (anti-tachycardia pacing (ATP) and ICD shock) decreased significantly after MitraClipTM implantation (1.0 ± 3.87 vs. 0.32 ± 1.41, p = 0.014). However, reduction of VA burden did not result in improved two-year survival in this patient cohort with severely reduced LVEF. Mitral valve TEER using the MitraClip™ device was associated with a significant reduction of ventricular arrhythmias and ICD therapies.
Im Text ist "TM" hochgestellt
Gesehen am 14.05.2022